Connexin 43 and Pannexin 1 hemichannels as endogenous regulators of innate immunity in sepsis - Li, Jianhua; Lou, Li; Chen, Weiqiang; Qiang, Xiaoling; Zhu, Cassie; Wang, Haichao (Frontiers in Immunology, 2024)
Sepsis is a life-threatening organ dysfunction resulting from a dysregulated host response to infections that is initiated by the body’s innate immune system. Nearly a decade ago, we discovered that bacterial lipopolysaccharide (LPS) and serum amyloid A (SAA) upregulated Connexin 43 (Cx43) and Pannexin 1 (Panx1) hemichannels in macrophages. When overexpressed, these hemichannels contribute to sepsis pathogenesis by promoting ATP efflux, which intensifies the double-stranded RNA-activated protein kinase R (PKR)-dependent inflammasome activation, pyroptosis, and the release of pathogenic damage-associated molecular pattern (DAMP) molecules, such as HMGB1. Mimetic peptides targeting specific regions of Cx43 and Panx1 can distinctly modulate hemichannel activity in vitro, and diversely impact sepsis-induced lethality in vivo. Along with extensive supporting evidence from others, we now propose that hemichannel molecules play critical roles as endogenous regulators of innate immunity in sepsis.